2019
DOI: 10.1620/tjem.248.151
|View full text |Cite
|
Sign up to set email alerts
|

Role Modeling for Female Surgeons in Japan

Abstract: Japan is still a patriarchal society. There is an increasing number of female doctors who wish to follow a career path in surgery. This new generation of female surgeons need support not only in their career but also in work-life balance, especially after they have a family. We founded the Japan Association of Women Surgeons (JAWS) with the aims to advance females in surgery by providing networking and to develop leadership, mentorship, education, expertise and advocacy. This article describes our philosophy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…• Learners emulate role models that they feel are closer to their own present identity ( 71 , 72 , 74 , 75 , 111 , 159 )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Learners emulate role models that they feel are closer to their own present identity ( 71 , 72 , 74 , 75 , 111 , 159 )…”
Section: Resultsmentioning
confidence: 99%
“…• Influences career choice ( 59 , 60 , 70 , 71 , 73 , 75 78 , 80 , 86 , 88 – 90 , 95 , 98 , 99 , 102 , 109 , 111 – 113 , 118 , 126 , 134 , 135 , 137 , 138 , 140 , 143 , 153 , 155 , 157 , 158 , 160 , 162 , 166 , 169 , 170 , 174 , 177 , 179 185 )…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Among these are surgical clerkship experiences and interactions with attending physicians and residents [ 16 ]. However, few literatures have studied the association between exposure to role models and decision to pursue a career in surgery [ 13 , 20 ]. It has been demonstrated that the influence of role models is a significant factor determining the choice of postgraduate training among medical students [ 8 , 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review [ 11 ] has extensively explored the factors affecting female surgeons in choosing their career; the evidence in local studies is, however, insufficient [ 12 ]. In a study conducted in Japan, female surgeons described the importance of having a role model to help them be more productive in their careers, although they indicated that finding the ideal model was difficult [ 13 ]. Another study in Virginia revealed that 35% of female medical students were discouraged from pursuing a surgical career because of the lack of female role models [ 4 ].…”
Section: Introductionmentioning
confidence: 99%